Photoresponsive Porphyrin Nanotubes of Meso-tetra(4-Sulfonatophenyl)Porphyrin and Sn(IV) meso-tetra(4-pyridyl)porphyrin - Koposova, Ekaterina A.; Offenhäusser, Andreas; Ermolenko, Yuri E.; Mourzina, Yulia G. (Frontiers in Chemistry, 2019)
Porphyrin macrocycles and their supramolecular nanoassemblies are being widely explored in energy harvesting, sensor development, catalysis, and medicine because of a good tunability of their light-induced charge separation and electron/energy transfer properties. In the present work, we prepared and studied photoresponsive porphyrin nanotubes formed by the self-assembly of meso-tetrakis(4-sulfonatophenyl)porphyrin and Sn(IV) meso-tetra(4-pyridyl)porphyrin. Scanning electron microscopy and transmission electron microscopy showed that these tubular nanostructures were hollow with open ends and their length was 0.4 - 0.8 μm, the inner diameter was 7 - 15 nm, and the outer diameter was 30 - 70 nm. Porphyrin tectons, H4TPPS42- : Sn(IV)TPyP4+, self-assemble into the nanotubes in a ratio of 2:1, respectively, as determined by the elemental analysis. The photoconductivity of the porphyrin nanotubes was determined to be as high as 3.1×10-4 S m-1, and the dependence of the photoconductance on distance and temperature was investigated. Excitation of the Q-band region with a Q-band of SnTPyP4+ (550 - 552 nm) and the band at 714 nm, which is associated with J-aggregation, was responsible for about 34 % of the photoconductive activity of the H4TPPS42- - Sn(IV)TPyP4+ porphyrin nanotubes. The sensor properties of the H4TPPS42- - Sn(IV)TPyP4+ nanotubes in the presence of iodine vapor and salicylate anions down to millimolar range were examined in a chemiresistor sensing mode. We have shown that the porphyrin nanotubes advantageously combine the characteristics of a sensor and a transducer, thus demonstrating their great potential as efficient functional layers for sensing devices and biomimetic nanoarchitectures.